Selective zygomaticus muscle activation by ball electrodes in synkinetically reinnervated patients after facial paralysis - Arnold, Dirk; Thielker, Jovanna; Klingner, Carsten M.; Guntinas-Lichius, Orlando; Volk, Gerd Fabian (Frontiers in Rehabilitation Sciences, 2023)
Introduction Although many different treatments were developed for facial palsy, only a few therapeutic options are available for facial synkinesis. Electrical stimulation of specific muscles via implants could be useful in restoring facial symmetry in synkinetic patients. A challenge in developing stimulation devices is finding the right stimulation location, type, and amplitude. This work assesses the ability to selectively stimulate the zygomaticus muscle (ZYG) in patients with oral-ocular synkinesis to elicit a visually detectable response of the ipsilateral corner of the mouth (COM), without causing a reaction of the orbicularis oculi muscle (OOM). We aimed to assess how close to the COM the stimulation should be delivered in order to be selective. Methods A total of 10 patients (eight females, two males) were enrolled. Facial function was graded according to the Sunnybrook facial grading system. Needle EMG was used to test the activities of the muscles, during volitional and “unintended” movements, and the degree of synkinesis of the ZYG and OOM. Two ball electrodes connected to an external stimulator were placed on the paretic ZYG, as close as possible to the COM. Results Independent of the waveform with which the stimulation was presented, a selective ZYG response was observed within 4.5 cm of the horizontal plane and 3 cm of the vertical plane of the COM. When the distance between the electrodes was kept to ≤2 cm, the amplitude necessary to trigger a response ranged between 3 and 6 mA when the stimulation was delivered with triangular pulses and between 2.5 and 3.5 mA for rectangular pulses. The required amplitude did not seem to be dependent on the applied phase duration (PD), as long as the PD was ≥5 ms. Conclusion Our results show that selective stimulation of the ZYG presenting synkinetic ZYG–OOM reinnervation can be achieved using a broad PD range (25–1,000 ms) and an average amplitude ≤6 mA, which may be further decreased to 3.5 mA if the stimulation is delivered via rectangular rather than triangular waves. The most comfortable and effective results were observed with PDs between 50 and 250 ms, suggesting that this range should be selected in future studies. Clinical Trial Registration [https://drks.de/search/de/trial/DRKS00019992], identifier (DRKS00019992).